Isolation and Phylogenetic Analysis of Reemerging Pseudorabies Virus Within Pig Populations in Central China During 2012 to 2019 - Hui-Hua Zheng (Frontiers Media S.A., 2021)
To understand the biological characteristics of the reemerging pseudorabies virus (PRV) strains, a total of 392 tissue samples were collected from diseased pigs during reemerging PR outbreaks between 2012 and 2019 on farms in central China where swine had been immunized with Bartha-K61 and 51 (13. 01%) were positive for the gE gene by PCR. Sixteen PRV strains were isolated and caused clinical symptoms and death in mice. Subsequently, gE, gC, gB, and gD complete genes were amplified from the 16 PRV isolates and sequenced. Phylogenetic analysis based on these four gene sequences shows that the 16 PRV isolates were more closely related to the Chinese PRV variants (after 2012) but genetically differed from early Chinese PRV isolates (before 2012). Sequence analysis reveals that PRV isolates exhibited amino acid insertions, substitutions, or deletions compared with early Chinese PRV isolates and European–American PRV strains. In addition, this is the first report that eight isolates (8/16) in this study harbor a unique amino acid substitution at position 280 (F to L) of the gC protein, and six isolates have an amino acid substitution at position 338 (A to V) of the gD protein compared with the Chinese PRV variants. The emulsion containing inactivated PRV NY isolate could provide complete protection against the NY isolate. This study might enrich our understanding of the evolution of reemerging PRV strains as well as pave the way for finding a model virus to develop a novel vaccine based on reemerging PRV strains.